Training in Business Ethics and Communication for The Barokah Samarinda Joint Business Group - Christie Stephanie Piar; Muhammad Nawawi; Suramli Suramli; Armini Ningsih; Della Olivia Caterina Kalangit; Sarwo Eddy Wibowo (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
This community service activity was carried out on December 9, 2023, which aims to provide training and guidance to the Bersama Barokah Business Group located in Dadi Mulya Village, Samarinda Ulu District, Samarinda City, about the importance of ethics and business communication in running a form of business. The method used is counseling and simulation (educational approach), namely in this activity, knowledge transfer is carried out and group discussions are also carried out about the importance of communication ethics in running a business. The result of this activity is that participants gain knowledge and understanding of the benefits they will receive when implementing communication ethics in running a business. From the results of the evaluation of implementation methods, usefulness and duration of training, training participants revealed that business ethics and communication were able to improve the skills of KUB members in providing maximum service, both internally and externally to customers.